The Influence of Digital Leadership and Organizational Culture on Digital Behavior with Digital Adoption as a Mediating Variable: A Study of Employees at the Transportation Agency of West Kalimantan Province - Nina Kartika; M. Irfani Hendri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of digital leadership and organizational culture on employees’ digital behavior, with digital adoption serving as a mediating variable. The research is grounded in the increasing demand for public institutions, particularly the Department of Transportation of West Kalimantan Province, to strengthen digital readiness in response to ongoing technological transformation in public services. A quantitative survey method was employed, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital leadership has a positive and significant effect on both digital adoption and digital behavior. Organizational culture also demonstrates a positive effect on digital adoption; however, its direct influence on digital behavior is weaker compared to its mediated effect. Furthermore, digital adoption significantly mediates the relationships between digital leadership and organizational culture with digital behavior. These findings highlight the importance of strengthening digital-oriented leadership and cultivating an adaptive organizational culture to enhance productive digital behavior within government institutions.